Kinematics Analysis of a Two-wheeled Robot on a Sphere - Lu Chenxi; Zhang Wenzhi; Chen Fumin (Jixie chuandong, 2020)
Abstract To study the motion control problem of the two-wheeled robot on the spherical container，the motion characteristics of the robot on the spherical surface are analyzed. For motion description，the motion of the robot in the three-dimensional environment is decomposed and projected into the two-dimensional coordinate plane by making a tangent plane and a normal plane at the center point of the robot. The trajectory and velocity of the robot on the spherical surface are obtained，and then the mathematical model of the robot's motion on the spherical surface is established. Finally，the kinematics model is discretized and simulated in Matlab.The feasibility of the model is verified by the simulation results, and the graphics of the simulation process visually shows the motion state of the robot, which provides theoretical help for the motion planning of the robot.